Epidemiological analysis of porcine reproductive and respiratory syndrome viruses in 2020–2023 in China and the impact of serum acclimatization on production performance of sows farm - Li, Shuangxi; Hua, Jinlian (Frontiers in Veterinary Science, 2025)
Porcine reproductive and respiratory syndrome (PRRS), caused by PRRS virus (PRRSV), leads to severe economic losses in the pig farming industry. Currently, there is no specific treatment for PRRSV. This study investigated the epidemiological characteristics of PRRSV in large-scale pig farms across 24 provinces and municipalities in China from 2020 to 2023. Subsequently, serum acclimatization of gilts was implemented in large-scale pig farms to evaluate its impact on the reproductive performance of sows and the growth performance of piglets. The results showed that 14 provinces had PRRSV-positive rates exceeding 10%, with Yunnan Province reporting the highest rate at 23.5%, whereas Zhejiang had the lowest at 3.5%. The PRRSV-positive rate exhibited clear seasonality, with markedly higher rates in winter and spring compared to summer and autumn. The introduction of gilts was identified as the most important cause of PRRS outbreaks, with an incidence rate as high as 49%. Following serum acclimatization, the average total number of piglets per litter, the average number of live piglets per litter, the number of piglets weaned per litter, and the total weaning weight per litter were all significantly higher than those before acclimatization and in unacclimated sows (p < 0.05). The results indicated that serum acclimatization could effectively improve the reproductive performance of sows and the growth performance of piglets. This study provides valuable data for understanding the epidemiology of PRRSV and supports serum acclimatization as a potential strategy for PRRSV prevention and control in China.